Analisis Media Sigil dan Lithium EPUB Reader dalam Pembelajaran Teks Eksposisi Kelas X Sekolah Menengah Atas Medan - Suherlinda, Suherlinda; Saragih, Sanrais Josua; Tanjung, Rezki Agus Pandai Yani; Surip, Muhammad; Dalimunthe, Syairal Fahmy (Jurnal Bahastra, 2025)
This study analyzes the use of Sigil and Lithium EPUB Reader as digital learning media in teaching expository texts to tenth-grade students at a senior high school in Medan. The central issue addressed in this research is the low level of students’ interest and comprehension of expository texts, largely due to the limited availability of interactive and engaging learning media. The study aims to examine the effectiveness of these two media in enhancing students’ comprehension of expository texts. A quantitative approach with a quasi-experimental design was employed, involving two groups: an experimental class using Sigil and Lithium EPUB Reader, and a control class taught through conventional methods. Data were collected using pre-tests and post-tests on text comprehension, as well as student response questionnaires. The findings reveal that the experimental class demonstrated a significant improvement in comprehension compared to the control group. Furthermore, students expressed positive responses toward the use of Sigil and Lithium EPUB Reader, noting that the media were more engaging, interactive, and facilitated their understanding of text structure and linguistic features. Consequently, Sigil and Lithium EPUB Reader can serve as effective digital alternatives to improve the quality of expository text learning in senior high schools.